Parametrische Steuerung — eine neuer Steuerungsmodus für die Raumplanung? - Cools, Marion; Gnest, Holger; Fürst, Dietrich (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
“Parametric governance” refers to a steering mode by which the steering body defines operationalized objectives but leaves it open to the implementing bodies how the goals may be achieved. Transferred to spatial planning that steering mode would require theLandesplanungnot to delineate areas with special purposes but just to indicate the objective, e.g.: The state stipulates regional planners to demarcate areas which are suitable and capable to host “x mega-watt of wind-energy”. The approach corresponds to newer governance patterns which grant the decentralized implementing agencies more room of manoeuvre to develop solutions which are better suited to the problems, more attuned to the given situation and more accepted by those concerned than the traditional top-down solutions. In particular, the approach is closely related to the mode of “contracting” within the system of new public management. The article tries to give an idea of the potentials of parametric governance for spatial planning and to derive knowledge from similar approaches in other policy areas or other fields of action as to what could improve the effectiveness of the approach and where to look for problems and obstacles.